Spin wave perturbation in rare-earth iron garnet thin films with epitaxial strain relaxation - EMK Ikball Ahamed; Md Shamim Sarker; Hiroyasu Yamahara; Siyi Tang; Kazuo Morikawa; Munetoshi Seki; Hitoshi Tabata (APL Materials)
This study investigates the effects of epitaxial strain on the crystal structure, magnetization, and spin wave propagation characteristics of rare-earth iron garnet thin films. Thin films of Y3Fe5O12 (YIG) and Lu3Fe5O12 (LuIG), each with identical thicknesses, are grown on Gd3Ga5O12 (GGG), substituted Gd3(GaMgZr)5O12 (SGGG), and Y3Al5O12 (YAG) substrates, causing systematic strain variation in films based on the substrate lattice constants. Exceeding a certain critical thickness for epitaxial strain relaxation, the strained epitaxy transitions to a relaxed state, and dislocations form at the boundary between the strained and relaxed phases. High-resolution scanning transmission electron microscopy reveals dislocations and missing atomic lines in relaxed films with large mismatches, which correlates with a reduction in saturation magnetization and an increase in Gilbert damping. Consequently, the spin wave transmission drops significantly more in relaxed YIG/YAG (large mismatch of +2.96%) and LuIG/YAG (+2.2%) films than in their strained counterparts. Remarkably, the tensile-strained films maintain their strain without relaxation, even with a large mismatch, confirming efficient spin-wave transmission. These findings emphasize the significant advantages of strained epitaxy for advanced spin wave-based magnonic device applications.